Destroy to save - Geoffroy de Clippel; Victor Naroditskiy; Maria Polukarov; Amy Greenwald; Nicholas R. Jennings (Brown University, Department of Economics, 2012)
We study the problem of allocating m identical items among n > m agents with unit demand and private value for consuming the good. We allow payments and focus on dominant-strategy implementation. In the absence of an auctioneer who can absorb payments collected from the agents, the payments must be burnt to support dominant-strategy implementation. Recent work modified the classic VCG mechanism by redistributing as much of the payments as possible back to the agents while still satisfying incentive constraints. This approach guarantees allocative efficiency, but in some cases a large percentage of social welfare is lost. In this paper, we provide a mechanism that is not allocatively efficient but is instead guaranteed to achieve at least 80% of the social welfare as n -> [...] Moreover, in the extreme case of m = n - 1 where VCG-based mechanisms provide zero welfare, the percentage of social welfare maintained by our mechanism asymptotically approaches 100%.
Keywords: 330